Antibacterial Effects of a 940 nm Diode Laser With/ Without Silver Nanoparticles Against Enterococcus faecalis: Antibacterial Effects of Diode Laser and Silver Nanoparticles - Hendi, Seyedeh Sareh; Poormoradi, Banafsheh; Shiri, Maryam; Alikhani, Mohammad Yousef; Afshar, Saeid; Farmani, Abbas; Moghadam Shakib, Masoud (Journal of Lasers in Medical Sciences, 2021)
Introduction: The final goal of root canal therapy is to remove most bacteria from the root canal. This study aimed at comparing the antibacterial effects of a diode laser with a wavelength of 940nm and silver nanoparticles and the synergic effects of both techniques on Enterococcus faecalis. Methods: Ninety single-rooted human teeth were decoronated and prepared with rotary files. The samples were irrigated with sodium hypochlorite and EDTA17%. Then they were autoclaved and contaminated with E. faecalis suspension (1.5 × 108 CFU/mL) for 21 days. The samples were fixed in a microtube and were randomly divided into 4 experimental (n=20) groups and a negative control group (n=10) as follows: Group 1: hypochlorite sodium 5%, Group 2: silver nanoparticle, Group 3: diode laser, and Group 4: diode laser and silver nanoparticle. The samples were obtained from dentin chips before and after the intervention. The data were analysed using the Kruskal-Wallis nonparametric test. Furthermore, alterations in bacterial colonies were entered using the Wilcoxon signed ranks test (α=0.05). Results: There was a significant decrease in colony counts for all groups after interventions (P value<0.05). Also, all groups showed more reductions in colony counts compared with the negative control group (P-value <0.004). There was a significant reduction for group 1 in comparison with other groups (P-value <0.001) and this group had an extreme decrease of colony counts (RCC=100%). There was an important differential between silver nanoparticles and diode laser groups in bacterial counts (P value<0.001) and silver nanoparticles (RCC=83.15%) had more efficiency than the diode laser (RCC=41/33%). RCC of group 4 was 68/52%. Conclusion: Followed by sodium hypochlorite 5%, silver nanoparticles were the most effective antibacterial substances. The 940 nm laser diode had less antibacterial effect compared to its use with silver nanoparticles. DOI:10.34172/jlms.2021.73